Online commercial sex-seeking among female sex workers in south China: a cross-sectional study - Zhao, Peizhen; Xu, Wenqian; Ye, Rouxuan; Shi, Yijia; Wang, Cheng (BMC infectious diseases, 2023)
Online communication platforms have the potential to facilitate commercial sex among female sex workers (FSW), increasing the risk of contracting sexually transmitted diseases (STD). This study aimed to describe the patterns of online commercial sex-seeking and examine the associated factors among FSW in China. A venue-based cross-sectional study was conducted in five cities in Guangdong Province, China, between April and October 2020. Data on socio-demographic characteristics, sexual behaviors, and online commercial sex-seeking patterns were collected through face-to-face interviews. Venous blood and urine samples were collected for STD testing. Univariate and multivariable logistic regressions were used to explore the factors associated with online commercial sex-seeking. A total of 1155 FSW were recruited in physical venues for this study. Among them, 33.42% reported ever using online applications to seek commercial sex. The prevalence of HIV, syphilis, gonorrhea, chlamydia, and STD was 0.26%, 1.30%, 4.40%, 15.54%, and 18.39%, respectively, among FSW who had ever used both physical and online venues to seek commercial sex, which was higher than among FSW who had never sought commercial sex online. Multivariable logistic regression indicated that FSW who used online platforms to seek commercial sex were more likely to have STD (adjusted odds ratio (aOR) = 1.48, 95%CI: 1.05-2.09), experience unintended pregnancies due to commercial sex (aOR = 1.78, 95%CI: 1.21-2.62), be diagnosed as infertile (aOR = 3.20, 95%CI: 1.42-7.21), and undergo abortions (aOR = 1.69, 95%CI: 1.29-2.20). A significant proportion of FSW who practiced in physical venues in China engaged in seeking commercial sex online, and this behavior is positively correlated with both STD and reproductive health outcomes. Given the high prevalence of online sex-seeking, it is crucial to provide a wide range of internet-based healthcare interventions and reproductive health services to Chinese FSW.